2019
DOI: 10.1007/s00590-019-02412-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term risk factors for a second hip fracture in a UK population

Abstract: Introduction A hip fracture carries significant morbidity and mortality—a second fracture of the contralateral hip carries even higher complications. Most second hip fractures occur within 48 months of the first. The aim of this study was to comprehensively analyse all identifiable variables that may increase the risk of a contralateral hip fracture within this time period. Methods We retrospectively analysed 1242 consecutive patients with hip fractures presenting to our institution. All patient-related, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
5
15
1
Order By: Relevance
“…Our results are also consistent with reported 30-d readmission rates for COPD (16.5-22.6%) [31,32,44], or DM (14.2-25%) [45][46][47][48]. Studies on osteoporotic fractures are heterogeneous regarding population age, examined diagnoses, and timeframe of readmissions [49][50][51][52][53] and they focus rather on surgical options [50], complications, or reoccurrence of hip…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are also consistent with reported 30-d readmission rates for COPD (16.5-22.6%) [31,32,44], or DM (14.2-25%) [45][46][47][48]. Studies on osteoporotic fractures are heterogeneous regarding population age, examined diagnoses, and timeframe of readmissions [49][50][51][52][53] and they focus rather on surgical options [50], complications, or reoccurrence of hip…”
Section: Discussionsupporting
confidence: 89%
“…Our results are also consistent with reported 30-d readmission rates for COPD (16.5-22.6%) [ 31 , 32 , 44 ], or DM (14.2-25%) [ 45 48 ]. Studies on osteoporotic fractures are heterogeneous regarding population age, examined diagnoses, and timeframe of readmissions [ 49 53 ] and they focus rather on surgical options [ 50 ], complications, or reoccurrence of hip fractures [ 49 , 51 , 53 ]. In our analysis, we chose a more holistic view and included cases diagnosed with OS (ICD-10 codes M80 and M81) independent of the occurrence of a fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 in our study demonstrates that for our cohort the risk of a second hip fracture is highest in the first year, with most of the remaining fractures occurring within five years of the initial hip fracture. These findings are supported by the literature where several studies have demonstrated that most contralateral hip fractures will occur within the first 48 months following an initial hip fracture [ 8 ]. However, Sobolev et al demonstrated that the risk of a contralateral hip fracture persists for at least 10 years following the initial hip fracture [ 10 ].…”
Section: Discussionsupporting
confidence: 78%
“…Incidence of second hip fractures is greater among older patients [232,234,235,237,247,248], and females [232,236,244,248]; other risk factors described are dementia, malnutrition, Parkinson's disease, cerebrovascular disease, hepatic disease, osteoporosis, intrahospital pneumonia, urinary tract infection, higher Charlson comorbidity index, increased length of stay (surrogate of comorbidity), initial trochanteric fracture and initial treatment with an arthroplasty [232,234,236,239,244,248,249], but also less dependent patients [250]. Patients using non-steroidal anti-inflammatory drugs (NSAIDs) have a higher dose-dependent risk of second hip fracture [247,248].…”
Section: Second Hip Fracturementioning
confidence: 99%
“…Patients using non-steroidal anti-inflammatory drugs (NSAIDs) have a higher dose-dependent risk of second hip fracture [247,248]. Some authors found no relation regarding destination at discharge [249], but others describe living in a nursing home as a risk factor [232]; Cabalatungan reported more patients with second hip fractures had been admitted from nursing homes [250].…”
Section: Second Hip Fracturementioning
confidence: 99%